Analisis Pengembangan E-Government (Studi E-Monev Badan Perencanaan Pembangunan Daerah Provinsi Sumatera Selatan Tahun 2021) - Agung Saputra; Simon Sumanjoyo Hutagalung; Intan Fitri Meutia (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2023)
This study aims to find out how the development of the E-Monev system for the Regional Development Planning Agency of South Sumatra Province in 2021 and what are the main factors that influence the development process carried out, based on the successful indicators of E-Government development from the United Nations Online Network in Public Administration and Finance that adjusts the conditions at the Regional Development Planning Agency of South Sumatra Province. The results of the study show that the development of the E-Monev system for the Regional Development Planning Agency of South Sumatra Province in 2021 has been considered successful, where by carrying out this development, it can improve the government management system and development management governance system in the province of South Sumatra, especially the increase in the performance system. more accountability and transparency, as well as the creation of a more effective and efficient development management system. The success of the development of the E-Monev system itself is influenced by various factors, such as the allocation of various resources (human, budget, information, energy, time), the construction of supporting infrastructure and superstructure that supports the performance of the South Sumatra provincial apparatus and the element of political will. the desire of politicians) from the leaders of the South Sumatra Province to make this system a superior system in supporting the process of governance management and development management in South Sumatra Province.